Hubungan Pengetahuan Gizi dan Kebiasaan Sarapan terhadap Prestasi Belajar Siswa di SMA Negeri 12 Kota Bekasi - Dwi Putri Yuniarsih (Jurnal Health Sains, 2021)
The quality of the nation is determined by one of the success rates of education which is carried out systematically and continuously from student learning outcomes. Optimal student learning outcomes depend on the provision of nutrition, both in terms of quality and quantity. Food nutrition at breakfast has affects student concentration and learning achievement in understanding learning at school. This study aims to determine the relationship between nutritional knowledge and breakfast habits on student achievement in SMA Negeri 12 Bekasi City. The research method used was a survey analytic study with aapproach cross- sectional. The sample in this study were 84 respondents. The subjects in this study were students in grade 10 and 11 aged 15-17 years. Sampling was done using a simple random sampling technique. The results of the study used Chi Square statistical test analysis with a significance limit of α = 0.05. Based on the results of the bivariate analysis, there is a significant relationship between nutritional knowledge and learning achievement with a p-value of 0.001 <α 0.05 and the OR= 5.174 also obtained. There is a significant relationship between breakfast habits and learning achievement with a p-value of 0.016 <α 0.05 and the OR = 3.145 is also obtained. So, the better the student's nutritional knowledge, the more concerned with the menu and food combinations for breakfast in the morning. This will affect the readiness of students to follow and remember the subject matter